Administrative secretary - 3G E-Learning LLC (New York, NY 3G E-Learning LLC, 2019)
As the reliance on technology continues to expand in offices, the role of the office professional has greatly evolved. Office automation, professional services automation and organizational restructuring have led secretaries and administrative assistants to increasingly assume responsibilities once reserved for managerial and professional staff. In spite of these changes, however, the core responsibilities for secretaries and administrative assistants have remained much the same: performing and coordinating an office's administrative activities and storing, retrieving, and integrating information for dissemination to staff and clients. Secretaries and administrative assistants perform a variety of administrative and clerical duties necessary to run an organization efficiently. They serve as information and communication managers for an office; plan and schedule meetings and appointments; organize and maintain paper and electronic files; manage projects; conduct research; and disseminate information by using the telephone, mail services, Web sites, and e-mail. They may also handle travel and guest arrangements.
includes index and bibliographical references
Keywords: Secretaries